Three-Month Follow-up Study of Mental Health Outcomes After a National COVID-19 Lockdown: Comparing Patients With Mood or Anxiety Disorders Living in an Area With a Higher Versus Lower Infection Incidence - Carmassi, Claudia; Dell'Osso, Liliana; Bertelloni, Carlo Antonio; Pedrinelli, Virginia; Dell'Oste, Valerio; Cordone, Annalisa; Ruggeri, Mirella; Schimmenti, Simone; Bonetto, Chiara; Tosato, Sarah (The journal of clinical psychiatry, 2022)
The COVID-19 pandemic and the related containment measures can represent a traumatic experience, particularly for populations living in high incidence areas and individuals with mental disorders. The aim of this study was to prospectively examine posttraumatic stress disorder (PTSD), anxiety, and depressive symptoms since the end of the first COVID-19 pandemic wave and Italy's national lockdown in subjects with mood or anxiety disorders living in 2 regions with increasing pandemic incidence. 102 subjects with a anxiety or mood disorder were enrolled from June to July 2020 and assessed at baseline (T0) and after 3 months (T1) with the Impact of Event Scale-Revised, Patient Health Questionnaire-9, Generalized Anxiety Disorder 7-Item, and Work and Social Adjustment Scale. At T1, subjects were also assessed by means of the Trauma and Loss Spectrum Self-Report for PTSD. At T0, subjects from the high COVID-19 incidence area showed higher levels of traumatic symptoms than those from the low COVID-19 incidence area (P < .001), with a decrease at T1 with respect to T0 ( = .001). Full or partial PTSD related to the COVID-19 pandemic emerged in 23 subjects (53.5%) from the high COVID-19 incidence area and in 9 (18.0%) from the low COVID-19 incidence area ( < .001). Subjects with mood or anxiety disorders presented relevant rates of PTSD, depressive, and anxiety symptoms in the aftermath of the lockdown, and in most cases these persisted after 3 months. The level of exposure to the pandemic emerged as a major risk factor for PTSD development. Further long-term studies are needed to follow up the course of traumatic burden.